Remaining Gap in HIV Testing Uptake among Female Sex Workers in Iran - Shokoohi, Mostafa (AIDS Behav, 2017)
We estimated the prevalence of recent HIV testing (i.e., having an HIV test during the last 12 months and knew the results) among 1,295 HIV-negative Iranian female sex workers (FSW) in 2015. Overall, 70.4% (95% confidence intervals: 59.6, 79.3) of the participants reported a recent HIV testing. Concerns about their HIV status (83.2%) was reported as the most common reason for HIV testing. Incarceration history, having >5 paying partners, having >1 non-paying partner, receiving harm reduction services, utilizing healthcare services, and knowing an HIV testing site were significantly associated with recent HIV testing. In contrast, outreach participants, having one non-paying sexual partner, and self-reported inconsistent condom use reduced the likelihood of recent HIV testing. HIV testing uptake showed a ~2.5 times increase among FSW since 2010. While these findings are promising and show improvement over a short period, HIV testing programs should be expanded particularly through mobile and outreach efforts.